Implementasi Konsep Moneter Islam Berdasarkan Pandangan M.Umar Chapra Terhadap Kebijakan Moneter Di Indonesia - Imsar, Imsar; Kurniawan, Muhammad (LPPM Universitas Labuhanbatu, 2023)
The method used by the author in this study is a qualitative method with the results presented in a descriptive form, namely by collecting data by carrying out a literature study from some written literature. A country's economic success is largely determined by the precise determination of monetary policy. The ultimate goal of this research is to maintain and maintain the country's economic stability. The main focus of this research is to discuss the thoughts of M. Umar Chapra in the field of Islamic monetary economics. The author finds that Chapra's economic thinking is a combination of traditional sciences, religious knowledge and modern economics. His thoughts are dominated by the field of macroeconomics because he is much involved in the world of the country's economy. Like other Muslim economists, Chapra emphasizes the importance of morals for a fair and healthy economy. The specialty of M. Umer Chapra's thought is his ability to mix and match Western economic concepts with Islamic values.